"Min stämma är såsom en flyktig fogels...": Eljakim Jacob Soldin – en dansk-judisk diktare i det gustavianska Sverige - Jansson, Eva-Maria (Nordisk judaistik/Scandinavian Jewish Studies, 2008)
Eljakim Jacob Soldin (born c. 1770, Berlin, d. after 1809 in Denmark) began his literary career as a composer of honorary commemoration poems for family members and royal persons. Having trained – according to his own statement – as a book printer, he gained access to Sweden in the mid 1780s as a private tutor in a Jewish family, and during his stay there, he published poems to members of the royal family, a vivid genre of literature in both Sweden and Denmark at this time in history. After his return to Copenhagen, he published additional poems, but also booklets within the Haskalah tradition. In this article, a short overview is given of his life and works, and the contents of his literary production is analysed, in particular with regards to his awareness of the ‘proper’ themes to make use of in his honorary poems.